Time-Dependent Changes in Moisture Content of Some Organic Matter Sources Used as Soil Conditioners - KARA, Zekeriya; YAKUPOĞLU, Tuğrul (ISPEC Journal of Agricultural Sciences, 2023)
In this research, organic wastes, quail manure, gyttja, leonardite and pigeon manure were used as materials. In this study is to examine the time-dependent moisture changes in some organic matter sources used as soil conditioners or organic fertilizers. The research was carried out under constant temperature in laboratory conditions using 52 saturation cups. According to the results obtained, the highest nitrogen (% 7.13), phosphorus (5318 µɡ ɡ-1) and potassium (21480 µɡ ɡ-1) concentration and organic matter (% 73.9) content were determined in quail manure. The lowest values for these variables (N: % 0.54; P: 1781 µɡ ɡ-1; K: 4170 µɡ ɡ-1; OM: % 55) were determined for leonardite. Time-dependent moisture loss was the least in quail manure, followed by pigeon manure, gyttja and leonardite, respectively. These results were explained by the fact that organic regulators contain organic matter. It may be recommended to apply quail manure and pigeon manure in arid and semi-arid regions, especially where horticultural cultivation is more common. It has a positive effect on the yield in horticultural agriculture as it has a positive effect on both plant nutrient content and soil available water.